2020
DOI: 10.1021/acs.jpcc.0c05571
|View full text |Cite
|
Sign up to set email alerts
|

Operando Observations of a Manganese Oxide Electrocatalyst for Water Oxidation Using Hard/Tender/Soft X-ray Absorption Spectroscopy

Abstract: A layered manganese oxide catalyst containing K+ cations [K/MnO x catalyst] was developed, and its ability to efficiently decompose water was demonstrated. Operando hard/tender/soft X-ray absorption fine structure (XAFS) techniques were used to investigate the function of the K/MnO x catalyst under working conditions. The Mn valency depended on the potential and the amount of K+ cation adsorption. Mn K-edge (hard X-ray) XAFS measurements for the K/MnO x catalyst suggested that the Mn in the catalyst was an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…Moreover, Sargent's group found that higher OER activity was closely related to the readier oxidation transition of 3d metals in NiFe-and FeCo-based oxyhydroxide catalysts by in situ soft and hard X-ray absorption spectroscopies. [130] Recently, Mn 3+ sites in layered d-MnO 2 were identified as the reaction sites for OER using operando X-ray absorption spectroscopy, [131] agreeing with previous conclusion deduced by kinetics analysis. [16] However, most of the current in situ techniques applied focus on the Ir-and Ru-based catalysts in acidic OER condition or nonprecious-metal-based catalysts under alkaline conditions.…”
Section: In Situ/operando Characterizationsupporting
confidence: 84%
“…Moreover, Sargent's group found that higher OER activity was closely related to the readier oxidation transition of 3d metals in NiFe-and FeCo-based oxyhydroxide catalysts by in situ soft and hard X-ray absorption spectroscopies. [130] Recently, Mn 3+ sites in layered d-MnO 2 were identified as the reaction sites for OER using operando X-ray absorption spectroscopy, [131] agreeing with previous conclusion deduced by kinetics analysis. [16] However, most of the current in situ techniques applied focus on the Ir-and Ru-based catalysts in acidic OER condition or nonprecious-metal-based catalysts under alkaline conditions.…”
Section: In Situ/operando Characterizationsupporting
confidence: 84%
“…The magnitude of EXAFS‐FT spectra and Ni K‐edge EXAFS fitting confirm the Ni−O bonds in the first coordination field and the Ni−Ni bonds in the second coordination field (Figure S12–S14). As displayed in Figure 1f, the Ni−O peak moves slightly to the left after delithiation treatment, which suggests that those catalysts of the average Ni−O length decrease compared to the LNO‐0 [15] . In the Fourier transformation (FT) spectra (Figure 1g), the Ni−Ni peak (2.54 Å) for LNO‐0 with increased intensity indicates distorted NiO 6 octahedrons without the Jahn–Teller effect.…”
Section: Resultsmentioning
confidence: 90%
“…Analysis by extended X-ray absorption fine structure (EXAFS) is a powerful tool to decide the local structures of Mn catalysts. In Fourier transforms of k 3 -weighted EXAFS oscillations (Figure ), the peaks of Mn–O and Mn–Mn for Na|MnO 2 , Na|MnO x -400, Mg|MnO 2 , and Mg|MnO x -400 were observed at the same positions as the δ-MnO 2 reference, indicating that the local structure of Mn species remained as birnessite-type even after heating. On the other hand, the heat treatments caused the decrease of Mn–Mn scattering intensity for both Na|MnO 2 and Mg|MnO 2 catalysts, meaning that the long-range structures for both catalysts were distorted by annealing.…”
Section: Resultsmentioning
confidence: 99%